2012
DOI: 10.1111/j.1528-1167.2012.03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy in patients with uncontrolled partial‐onset seizures treated with adjunctive lacosamide: Results from a phase III open‐label extension trial

Abstract: and xUCB Pharma, Raleigh, North Carolina, U.S.A. SUMMARYPurpose: To evaluate the long-term (up to 5 years exposure) safety and efficacy of lacosamide as adjunctive therapy in patients with uncontrolled partial-onset seizures taking one to three concomitant antiepileptic drugs (AEDs) in open-label extension trial SP756 (NCT00522275). Methods: Patients who completed the double-blind trial SP754 (NCT00136019) were eligible to participate in this open-label extension trial (SP756). At the conclusion of trial SP754… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
79
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 11 publications
(15 reference statements)
16
79
0
4
Order By: Relevance
“…Levetiracetam was associated with the highest retention rates, with 60–75% of patients continuing treatment at 1 year. Most recently, results from open‐label extensions to Phase 3 double‐blind, placebo‐controlled trials have been reported for the ‘third‐generation’ AEDs lacosamide (LCM) 15 and perampanel (PER) 16. Outcomes were consistent with those reported in the meta‐analysis of second‐generation AEDs.…”
Section: Discussionsupporting
confidence: 58%
“…Levetiracetam was associated with the highest retention rates, with 60–75% of patients continuing treatment at 1 year. Most recently, results from open‐label extensions to Phase 3 double‐blind, placebo‐controlled trials have been reported for the ‘third‐generation’ AEDs lacosamide (LCM) 15 and perampanel (PER) 16. Outcomes were consistent with those reported in the meta‐analysis of second‐generation AEDs.…”
Section: Discussionsupporting
confidence: 58%
“…The approval of LCM as adjunctive therapy in focal epilepsy was based on the results of three pivotal trials,13, 14, 15 all followed by open‐label extensions 16, 17, 18. In the pivotal trials, patients with highly refractory disease received LCM in a fixed titration scheme added to a variety of AEDs—up to 82% had a SCB in their treatment regimen 9, 19.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on adjunctive therapy with lacosamide for partial-onset seizures in adult patients: the researcher identified 32 citations, but only nine studies were included in the review: three randomized controlled trials published in peer-reviewed journals14-16, three open-label extension studies published as abstracts (Ben-Menachem et al, 2009;Rosenfeld et al, 2009;Faught et al, 2010;Husain et al, 2010), one economic evaluation published in a peer-reviewed journal (Bolin et al, 2010), and two economic evaluations published as abstracts (one of which also included a budget impact analysis) Soini et al, 2009). Studies were excluded because of one or more of the following reasons: disease other than refractory epilepsy; study not involving lacosamide; study of intravenous lacosamide; study of pharmacodynamic and/or pharmacokinetic profile of lacosamide; literature review rather than original study; case study.…”
Section: Search Resultsmentioning
confidence: 99%
“…Adverse events were reported to be of mild or moderate intensity. Three open-label extension studies of the pivotal trials explored the long-term safety, tolerability and efficacy of lacosamide (see Table 1) (Ben-Menachem et al, 2009;Rosenfeld et al, 2009;Faught et al, 2010;Husain et al, 2010). Long-term treatment with lacosamide produced a sustained efficacy in and was generally well tolerated by patients suffering from partial-onset seizures.…”
Section: Safety Tolerability and Efficacymentioning
confidence: 99%